Serologic Investigations in Children with Inflammatory Bowel Disease and Food Allergy - Urszula Grzybowska-Chlebowczyk; Halina Woś; Aleksander L. Sieroń; Sabina Więcek; Aleksandra Auguściak-Duma; Halina Koryciak-Komarska; Joanna Kasznia-Kocot (Mediators of Inflammation)
The aim of the study was the evaluation of frequency and titre of IgA ASCA and IgG ASCA and p-ANCA, c-ANCA in children with IBD and occurrence of ASCA antibodies in relation to coexistence of FA. Patients and methods. The study comprised 95 children at the ages of 2 to 18 years. The diagnosis of IBD was established on the basis of Porto criteria. Tests of blood serum were performed in all children: IgA and IgG ASCA, p-ANCA, c-ANCA using ELISA method. Results. IgE-dependent FA was found in 32.5% children with UC and in 21% with CD. We did not observe any relation between the occurrence of FA and the frequency and ASCA titre. p-ANCA were significantly more frequent in the group of children with UC. The occurrence of ASCA antibodies was observed in 73.7% of children with CD, 17.5% with UC and almost 30% with allergic colitis. Conclusions. Patients with CD and the presence of ASCA revealed a significantly more frequent localization of lesions within the small bowel and a tendency towards older age. We observed a connection between the occurrence of antibodies and the examined mutations of gene NOD2/CARD15.